Penginjilan Lintas Budaya - Hinadaka, Jon Jusuf (Sekolah Tinggi Teologi Borneo, 2023)
Abstract: strategy used for the approaching of a culture is not proffing that there is a standard pattern or method which used for evangelism. In the aplication of evangelism, every methods or pattens are always flexible. It depends on the tribe or culture which being the target of the evangelism itself. The objective of the church is to make all nations to be the disciple of Christ and to teach all disciples to obey the words of God (Mathew 28:19-20). The Gospel will be preached to the end of the world (Act 1:8). “So that at the name of Jesus every knee shall bow in heaven and on earth and under the earth, and every tongue confess: “Jesus Christ is Lord,” to the glory of God, the Father”. That is the aim of cross cultural evangelism.Keywords: Evangelism, Contextualization and Social ServiceAbstrak Sejarah penginjilan gereja untuk misi lintas budaya dalam pola-pola maupun strategi yang dipakai bagi pendekatan terhadap suatu budaya tertentu, tidak menunjukkan adanya suatu pola atau metode-metode baku yang dipakai secara khusus dalam penginjilan.Setiap metode atau pola selalu fleksibel dalam aplikasinya tergantung kepada suku atau budaya yang menjadi fokus atau tujuan misi itu sendiri. Tugas gereja adalah menjadikan semua bangsa menjadi murid Kristus dan mengajarkan murid Tuhan untuk dapat melakukan firman Tuhan. (Mat. 28:19-20). Injil Kristus diberitakan sampai ke ujung bumi (Kis. 1:8). “supaya dalam nama Yesus bertekuk lutut segala yang ada di langit dan yang ada di atas bumi dan ada di bawah bumi, dan segala lidah mengaku: “Yesus Kristus adalah Tuhan,” bagi kemuliaan Allah, Bapa!” inilah tujuan dari penginjilan lintas budaya tersebut.Kata Kunci: Penginjilan, Kontekstualisasi dan Pelayanan Sosial